An experimental study of the lift and drag of single wedge sections in two dimensional transonic flow using the hydraulic analogy - Bugler, J. W. (College of Aeronautics, 1960)
The similarity of the differential equations of the transonic flow of a gas in two dimensions and of the flow of shallow water led to the choice of the latter as on experimental method, to determine the pressure distribution, lift and drag on wedges with total angles of 10o , 15 o and 20 o. The wedges were towed through shallow water and the wave pattern was determined by the measurement of water depth using a photographic technique. The results have been compared with theory and with wind tunnel experiments. For the 10 o and 15 o wedges the trends for a range of angles of incidence agree with the predictions from transonic small disturbance theory, whereas those for the largest wedge of 10 o semi-angle indicate that this angle is too large to expect satisfactory experimental results. The trends are also similar to those obtained by other workers in a wind tunnel.